Greater Biomass Accumulation at Anthesis Increases Nitrogen Use Efficiency in Winter Wheat. (1st July 2019) - Brasier, Kyle; Oakes, Joseph; Balota, Maria; Thomason, Wade; Griffey, Carl
Abstract : Soft red winter wheat ( Triticum aestivum L.) production relies on efficient nitrogen (N) fertilization to maximize grower profitability and mitigate environmental impacts. Therefore, a panel of 11 elite wheat lines were grown as a randomized complete block design in four environments under low (LN) and high (HN) N rates to: (i) assess the genotypic variation in aboveground biomass (AGBM) and N yield (AGNY) throughout the growing season; and (ii) investigate the associations between yield and N‐related traits with AGBM and AGNY at tillering, booting, anthesis, and physiological maturity. Biomass samples were cut at the soil level and dried at four developmental stages to determine AGBM then ground to estimate AGNY for each sample. Significant genotypic variation ( P ≤ 0.05) was observed for grain yield, grain N content, and N‐utilization efficiency in all testing environments. Additionally, significant ( P ≤ 0.05) variation for AGBM and AGNY was identified at the five‐tiller stage, booting, anthesis, and physiological maturity in one or more testing environments. Grain yield was not significantly correlated with any trait under LN conditions despite expressing significant association with N‐utilization efficiency, N‐harvest index, AGBM at anthesis, and AGNY at anthesis under HN rates. Significant correlations also were identified for traits between LN and HN rates including AGBM at anthesis ( r = 0.93, P < 0.001) and AGNY ( r = 0.69, P < 0.01). Our results suggest that breeders can improve grain yields by using AGBM at anthesis as a proxy trait. Core Ideas Genotypic variation was observed in grain yield and N content, N‐utilization, biomass, and N yield. Grain yield correlated with aboveground biomass and aboveground N yield at anthesis under high N rates. Breeders can improve yields by using biomass at anthesis as a proxy trait per its strong correlation with N rates.